2019
DOI: 10.1002/maco.201911338
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of Cu–Sn bronze alloys in simulated archeological soil media

Abstract: The corrosion behavior of synthetic Cu–Sn bronze alloys with six different Sn contents was examined through an electrochemical test and a synthetic test in a simulated corrosive medium. The mechanism of corrosion and the morphology of the corroded surfaces were characterized through field emission scanning electron microscopy equipped with energy‐dispersive spectroscopy. At the corrosion potential, the corrosion behavior appears to be determined by the charge transfer step and the diffusion process. It was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…Furthermore, corrosion products enter the electrolyte more easily, making the diffusion process almost without obstacles. The equivalent circuit parameters listed in Table S2 prove this view, that is, the electrolyte resistance (R 1 ) decreases but the hindrance of the oxide film (R 2 ) is almost unchanged, and the charge transfer resistance (R 3 ) decreases sharply [44]. The above evidence shows that the addition of hydrogen peroxide can indeed accelerate the corrosion of brass, and EIS is consistent with the conclusion of potentiodynamic polarization, which is consistent with the inference of microscopic characterization.…”
Section: Corrosion Behavior Of H62 Brassmentioning
confidence: 71%
“…Furthermore, corrosion products enter the electrolyte more easily, making the diffusion process almost without obstacles. The equivalent circuit parameters listed in Table S2 prove this view, that is, the electrolyte resistance (R 1 ) decreases but the hindrance of the oxide film (R 2 ) is almost unchanged, and the charge transfer resistance (R 3 ) decreases sharply [44]. The above evidence shows that the addition of hydrogen peroxide can indeed accelerate the corrosion of brass, and EIS is consistent with the conclusion of potentiodynamic polarization, which is consistent with the inference of microscopic characterization.…”
Section: Corrosion Behavior Of H62 Brassmentioning
confidence: 71%
“…[ 39 ] The increase of defects means that an accelerated channel is provided for the migration of cations from the base alloy and the penetration of anions, such as Cl − and SO 4 2− , in the electrolyte, thus determining the corrosion resistance of the passivation film. [ 42 ] Therefore, the brass alloy passive film formed at a lower passive potential has stronger resistance to corrosion than the passive film formed at a higher passivation potential. These results are consistent with EIS measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The cyclic voltammograms showed that A. annua reduces anodic charges on the ALA coupon surfaces and decreases the surface film thickness from 1.00 nm (for ASW) to 0.21 nm (for 1 g L −1 AAE, Table 2 ). Since the magnitude of j corr represents the speed of the reaction [ 91 ], results indicated that the rate of dissolution of Al alloy 5083 was lower when the AAE was added to ASW, probably as a consequence of the adsorption of AAE molecules on the ALA surface that blocked the active sites of the material. This was supported by the calculated values of surface coverage, where during the addition of 1 g L −1 AAE to ASW, 0.786 of the ALA surface was covered with AAE molecules ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%